1994
DOI: 10.1002/1097-0142(19941001)74:7<1933::aid-cncr2820740718>3.0.co;2-x
|View full text |Cite
|
Sign up to set email alerts
|

Synchronous and metachronous head and neck carcinomas

Abstract: Background. The incidence of head and neck cancer is increasing. To improve the survival of head and neck cancer patients, an effective program of screening and/or chemoprevention of second malignancies is essential. An analysis of the incidence, time to development, and risk factors of second malignant tumors in head and neck cancer patients can contribute to the design of effective screening and chemoprevention programs. Methods. Eight hundred, fifty‐one patients with initial squamous cell carcinoma of the l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

21
173
1
8

Year Published

1998
1998
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 350 publications
(206 citation statements)
references
References 14 publications
21
173
1
8
Order By: Relevance
“…Parallel to their report 8.1 % of patients in current study presented with second primary, considering the limited median follow up period of 32 months in our series; this proportion might certainly increase. Development of second primary was associated with poorer outcome in oral hybrid VC as revealed in current series, this finding were parallel to the study by Schwartz et al [15] and Hordyk, G. J., et al [16] who reported poor prognosis in head and neck carcinomas associated with second primary cancer.…”
Section: Discussionsupporting
confidence: 91%
“…Parallel to their report 8.1 % of patients in current study presented with second primary, considering the limited median follow up period of 32 months in our series; this proportion might certainly increase. Development of second primary was associated with poorer outcome in oral hybrid VC as revealed in current series, this finding were parallel to the study by Schwartz et al [15] and Hordyk, G. J., et al [16] who reported poor prognosis in head and neck carcinomas associated with second primary cancer.…”
Section: Discussionsupporting
confidence: 91%
“…The incidence of multiple primary cancers of the hypopharynx has been reported to be approximately 10% -20% in Japan (Ogawa et al 1999), and the estimated 5-year metachronous cancer incidence rate has been found to be 34.4% (Schwartz et al 1994). In our study, 23 out of 74 patients had multiple primary cancers (31%).…”
Section: Discussionmentioning
confidence: 99%
“…Although radical surgery with subsequent reconstruction of the cervical esophagus by free jejunum transfer has become a relatively easy procedure for advanced cancer recently, the survival rate in such cases remains fairly poor. In hypopharyngeal cancer, there are various problematic issues such as the high frequency of distant metastasis, occurrence of multiple primary cancers (Schwartz et al 1994;Ogawa et al 1999), choice of therapy such as radiation and surgery for the primary lesion, therapy for retropharyngeal lymph node (Hasegawa and Matsuura 1994), and indication for contralateral elective neck dissection (Nishijima et al 1991;Anderson et al 1996;Lassaletta et al 2002). We thought that these many problems are compound and make survival rate decline.…”
mentioning
confidence: 99%
“…The hypothesis was supported by subsequent clinical and molecular studies (Chung et al 1993;Buller et al, 1998;Sozzi et al, 1995). The SPTs in patients with HNSCC have become an important clinical issue because of the increasing incidence of SPTs in head and neck cancer and the negative impact of such tumors on long-term survival of patients (Vokes et al, 1993;Jones et al, 1995;Schwartz et al, 1994). It is important to learn more about the molecular mechanisms of developing of SPTs to establish new strategies to treat patients with HNSCC and to prevent SPT development.…”
mentioning
confidence: 99%